(untitled) (Advancements in Homeopathic Research, 2023)
Introduction: Acid peptic disorder (APD) is a condition which includes peptic ulcer and gastro esophageal reflux disease (GERD). The highest prevalence rate of gastric disorders had been found out between ages 45-50. Dyspepsia is a term used for reduced digestion or indigestion. GERD is referred to as condition where there is regurgitation of stomach contents to the esophagus. Around 58.7% of peoples are having acid regurgitation or heart burn yearly once and 19.8% weekly once. Worldwide functional gastrointestinal disorder are commonest now a days, Irritable Bowel Syndrome (IBS) is also one among them having frequent pain abdomen and altered bowel habits without any structural gut abnormalities. Homoeopathy is a system which is based on individualization, and has principles of “Like cures like” and law of nature. Materials and methods: A retrospective study had been conducted with those patients who had attended the gastroenterology OPD of NHRIMH, Kottayam, Kerala, for a period of 1 year (from January 2022 to December 2022). Data had been collected from the case records and it had been found that around 899 patients had visited for the symptoms like nausea, vomiting, abdominal pain, altered bowel movements (diarrhea and constipation), bleeding per rectum, dysuria and hesitancy in urination,etc for the past 1 year. Aim of the study is to find out the most frequent age group, diseases affected and to know the frequently indicated remedies in treating gastroenterology disorders. Results: 899 patients visited in the defined period with a highest number of patients (212) were from the age group of 51-60, female patients were more than male patients, 758 old patients and 141 new patients. 214 pateints had diagnosed as gastritis which is the highest frequency noted. The most frequently indicated remedies were Nuxvomica in 161 patients and Suphur in 118 patients. Conclusion:It is concluded from the study that gastritis is the most common condition among patients visiting the above OPD in the defined period and Nux vomica, Sulphur and Lycopodium were the most common indicated and prescribed remedies.